FENOMENA KEMATIAN DALAM HIKAYAT RAJA JUMJUMAH: Sebuah Analisis Semiotika-Pragmatis Charles Morris - Maman, Maman (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2023)
Hikayat Raja Jumjumah is a classic Malay literary work with a religious theme which contains signs of an interesting readership and receives responses, both domestically and abroad. The purpose of this study is to reveal the description of the meaning of